Effect of the organic fertilizer Peat wheat and extracted it in growth and yield of eggplant - AL- Dhami, Ahmed S.M.; Al-lamy, Khalid A. M. (Journal of Kerbala for Agricultural Sciences, 2018)
A field experment was carried out to study effect of organic manure (wheat residues) and the filtrate extracted from it and the interactionbetween them in the growth and the yield plant eggplant in the field experiment of the spring 2014 season in one of the farms Dujailah area in Wasit province. Add compost in the soil four levels) 0، 10، 20 and 30 tons. ha-1(which weredesignate O1, O2, O3 and O4 respectively, also add Abstract Organic spraying method at rates three) 0, 2 and 4 ml. Liter-1(which was designat S1, S2 and S3 respectively. The experiment was adopted as factorial at Randomized Complete Block Design (R.C.B.D) with three replicates. The differences between means were tested by Duncan's Multiples Range Test ( D.M.R.T) at probability of 0.05. The results showed that the addition of compost and spraying the Organic extract has affected significantly in the parameters vegetative growth of plant height, number of branches of the main plant, leaf area, content leavesof chlorophyll, yield parameters(fruit weight, number of fruits. Plant -1, one plant yield, and total yield) compared with treatment without added.Increased influence the greater the amount of fertilizer added. The overlapping factors of the study significantly affected, as it gave the treatment of interactionO3S2 (Add compost level of 30 tons.ha-1+extract Organic concentration of 4 ml. Liter -1), the highest values ​​for all parameters the study has been amounted (94.41 cm plant -1,8.11 branch. plant -1, 447.5 dcm2. plant -1,64.88 SPAD units ,197.3 g. fruit -1,8.63 fruit. plant -1 and 1.703 kg. plant -1 and 36.61 tons. ha-1) respectively, compared to the treatment ofO0 S0 (without fertilization), which gave the lowest rate for those parameters .